A multi-center evaluation of a powered surgical stapler in video-assisted thoracoscopic lung resection procedures in China - Qiu, Bin; Yan, Wanpu; Chen, Keneng; Fu, Xiangning; Hu, Jian; Gao, Shugeng; Knippenberg, Susan; Schwiers, Michael; Kassis, Edmund; Yang, Tengfei (Journal of Thoracic Disease; Vol 8, No 5 (May 01, 2016): Journal of Thoracic Disease, 2016)
Background: Lung cancer is one of the most prevalent malignancies worldwide. The number of anatomic lung cancer resections performed via video-assisted thoracoscopic surgery (VATS) is growing rapidly. Staplers are widely used in VATS procedures, but there is limited clinical data regarding how they might affect performance and postoperative outcomes, including air leak. This clinical trial assessed the use of a powered stapler in VATS lung resection, with a primary study endpoint being occurrence and duration of air leak and prolonged air leak (PAL). Methods: Data was collected from a single arm, multi-center study in Chinese patients receiving VATS wedge resection or lobectomy. Intra-operative data included surgery duration; cartridge selection for ligation/transection of bronchus, major vessels, and lung parenchyma; staple line interventions; blood loss; and device usage. Post-operative data included air leak assessments, chest tube duration, length of hospital stay, and adverse events (AEs). Results: A total of 94 procedures across four institutions in China were included in the final analysis: 15 wedge resections, 74 lobectomies, and five wedge resections followed by lobectomies. Post-operative air leak occurred in five (5.3%) patients who had lobectomy procedures, with PAL in one (1.1%) patient. Sites were generally consistent relative to cartridge use by tissue type. The incidence of stapler firings requiring surgical interventions was seven out of 550 (1.3%). Surgeons participating in the study were satisfied with the articulation and overall usability of the stapler. Conclusions: The powered staplers make the VATS procedure easier for the surgeons and have achieved intra- and post-operative patient outcomes comparable to those previously reported.